Edukasi dan Pemberian Makanan Pendamping Air Susu Ibu (MP-ASI) Sebagai Upaya Peningkatan Gizi Balita di Desa Lolo Kabupaten Sigi - Buchair, Nur Hikmah; Laba, Stefiani Bengan (JURNAL PENGABDIAN FARMASI DAN SAINS, 2024)
The problem of toddler nutrition is still unresolved in Indonesia. Improper provision of MPASI is one of the factors that causes growth disorders and malnutrition. This service aims to increase knowledge and understanding regarding complementary foods for breast milk (MP-ASI) from mothers with babies/toddlers in the Lolu Village area, Biromaru District, Sigi Regency. The method used in this service is the lecture and question and answer method. The team also distributed the porridge of chicken moringa MPASI as an example of MPASI made from local food. The service activities went well and achieved the expected goals, where the community could understand the educational activities well and have a positive attitude towards imitating MPASI from local foods.